2012
DOI: 10.1186/1471-5945-12-7
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of skin diseases in a rural setting in Cameroon (sub-Saharan Africa)

Abstract: BackgroundSkin disorders are generally considered to be more prevalent in the rural areas of Cameroon. This study was carried out to verify this assumption by describing the spectrum of skin disorders in a rural setting of Cameroon.MethodsWe carried out a community-based clinical skin examination of 400 consenting subjects from 4 villages of Cameroon: Nyamanga (27%), Yebekolo (24%), Mbangassina (23%) and Bilomo (26%).ResultsThe overall prevalence of skin diseases in our sample was 62% {95% CI: 57.2%, 66.8%} (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
52
6
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 13 publications
12
52
6
4
Order By: Relevance
“…The prevalence of 11.2% in this study is higher than other general population studies done elsewhere in Africa, which reported a prevalence of 0.1–8.9% . There is a wide variation in the prevalence of acne in Africa.…”
Section: Showing the Characteristics Of 133 Patients With Acnecontrasting
confidence: 72%
“…The prevalence of 11.2% in this study is higher than other general population studies done elsewhere in Africa, which reported a prevalence of 0.1–8.9% . There is a wide variation in the prevalence of acne in Africa.…”
Section: Showing the Characteristics Of 133 Patients With Acnecontrasting
confidence: 72%
“…The 41% prevalence of scabies infestation recorded at the MPP is particularly high compared with the 2.8% prevalence registered among inhabitants of a rural setting in the Mbam Division, Centre region of Cameroon [13]. Likewise, our prevalence is higher than the 8.4% observed by Mbuagbaw et al after a study conducted in Yaoundé in the early 90s [18].…”
Section: Discussioncontrasting
confidence: 51%
“…Another survey undertaken by Bissek et al showed a 2.8% prevalence of scabies in a Cameroonian indigenous rural population [13]. However, few data are available regarding the prevalence and magnitude of scabies among groups at risk such as prisoners in Cameroon.…”
Section: Introductionmentioning
confidence: 99%
“…Human scabies toped the scale of dermatosis in our study (57.1%), which concurs with results from Kouotou et al (41%) (4). By contrast, a very low prevalence of scabies (2.8%) was obtained from a survey conducted in a rural community in the Mbam division, Cameroon (12). This high prevalence of scabies in our prisons suggests a frequent and prolonged contact between detainees, considering that the transmission of scabies is mostly through inter-human contact.…”
Section: Discussionmentioning
confidence: 97%